Racismo e resistência à discriminação: uma contribuição ao estudo das lutas sociais das negras e dos negros da classe trabalhadora - Santos, Diogo Joaquim dos (2016)
In this Master's thesis I aimed to understand the social struggles of black women and men of working class, especially with regard to the organizational forms of struggle and resistance against discrimination in the labor market. For this purpose, I get into first chapter on the debate about particularity and universality, in order to highlight, then the forms of resistance against racism, discussing the aspect of consciousness and ideology. In the second part of the dissertation, I retrieved the history of racism, relating it to the history of class societies, in order to point out the social and historical construction of the concept of 'race' in the face of changes in modes of production that rendered capitalism globally. Therefore, the 'racial' ideas here appear as classist and racist inventions themselves to the development of bourgeois relations of production. In turn, the known 'racial question', designed decoupled and independent of the social question, emerges as an aspect of dispersion of class perspective, being necessary to question their assumptions. Among them, an essential debate is understood, that is, as the Brazilian case, about the lucubrations about 'miscegenation' and 'social mobility'. In the last chapter, therefore, I discuss the social reality and the central aspects of social struggles of black women and men of working class, some demands and perspectives of struggle, passing the post-abolition period, the context of structural crisis of capital and resumption of neoconservative policies that are proposed as means of 'combat' racism, but aimed at underpinning the co-optation of social movements around formal and insignificant guarantees. In general, the conclusions expressed the view that strengthening the resistance of those individuals is central to the struggle for human emancipation, and has the assumption to overcome the fragmentation in which they are